Figure 1 from: Juswara L, Schuiteman A, Droissart V (2016) Four new orchid species from the Lengguru fold belt, West Papua, Indonesia. PhytoKeys 61: 47-59. https://doi.org/10.3897/phytokeys.61.7590 - Juswara, Lina; Schuiteman, Andre; Droissart, Vincent (Zenodo, 2016)
Figure 1 - Main localities sampled during Lengguru 2014 expedition and distribution of the four new species in West Papua, Indonesia.